2022
DOI: 10.3390/su14159440
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Approaches to Responsible Entrepreneurship Education

Abstract: This article explores innovations in and pedagogical approaches to Responsible Entrepreneurship Education (REE), with a specific focus on how to advance responsible entrepreneurial competencies (“know-how”) and entrepreneurial practices (“know-that”). Consequently, this article proposes the “4Rs” framework (re-imagining, reconfiguring, reshaping, and reforming) to guide entrepreneurship educators’ actions. Firstly, it is necessary to “re-imagine” the intended and enacted curriculum to develop a contemporary aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 96 publications
1
4
0
Order By: Relevance
“…Students who participate in entrepreneurship learning tend to have a greater intention to become entrepreneurs than students who do not participate in entrepreneurship learning. This finding corresponds with the findings of Igwe et al (2022), although the results show that there is no significant difference in entrepreneurial intentions of business students who participate in entrepreneurship education and students who do not, though this study reveals that the number of students who take entrepreneurship courses is slightly higher among those who do not participate. In contrast, Herman (2019) found that student participation in entrepreneurship education has no significant effect on students' entrepreneurship intentions.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Students who participate in entrepreneurship learning tend to have a greater intention to become entrepreneurs than students who do not participate in entrepreneurship learning. This finding corresponds with the findings of Igwe et al (2022), although the results show that there is no significant difference in entrepreneurial intentions of business students who participate in entrepreneurship education and students who do not, though this study reveals that the number of students who take entrepreneurship courses is slightly higher among those who do not participate. In contrast, Herman (2019) found that student participation in entrepreneurship education has no significant effect on students' entrepreneurship intentions.…”
Section: Discussionsupporting
confidence: 90%
“…Broadly speaking, the entrepreneurial process is divided into two phases, namely Phase 1, which represents the "know-how" learning process, and Phase 2, which represents the "practical process", which is directed at problem-solving and value creation (Igwe et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations